Idem Dito Nieuwsbrief. - Homocentrum Idem Dito (Brugge : Idem Dito, 1997)
Fonds Suzan Daniel (FSD)
Periodiciteit : onregelmatig
Redactie : PB 131, 8000 Brugge 1
Laatste nummer : 1/10/1999
Nederlands
Periodiek